Answer:
2
Step-by-step explanation:
<u>Given AP where:</u>
<u>To find</u>
<u>Since</u>
- a₄ = a₁ + 3d
- a₂ = a₁ + d
- a₆ = a₁ + 5d
<u>Initial equations will change as:</u>
- a₁ + 3d = 2(a₁ + d) - 1 ⇒ a₁ + 3d = 2a₁ + 2d - 1 ⇒ a₁ = d + 1
- a₁ + 5d = 7 ⇒ a₁ = 7 - 5d
<u>Comparing the above:</u>
- d + 1 = 7 - 5d
- 6d = 6
- d = 1
<u>Then:</u>
- a₁ = d + 1 = 1 + 1 = 2
- a₁ = 2
The first term is 2
Answer:
1. yes
2. NO
3.NO
4.NO
Step-by-step explanation:
A) 950, 900, 1000
b) 1860, 1900, 2000
c) 200, 200, 0
d) 650, 600, 1000
e) 19900, 19900, 20000
A = 2+3a +6
a-3a = 8
-2a = 8
a = -8/2 = -4
Answer:
d 7/4
Step-by-step explanation: